2012
DOI: 10.1371/journal.pone.0043802
|View full text |Cite
|
Sign up to set email alerts
|

Pentamers Not Found in the Universal Proteome Can Enhance Antigen Specific Immune Responses and Adjuvant Vaccines

Abstract: Certain short peptides do not occur in humans and are rare or non-existent in the universal proteome. Antigens that contain rare amino acid sequences are in general highly immunogenic and may activate different arms of the immune system. We first generated a list of rare, semi-common, and common 5-mer peptides using bioinformatics tools to analyze the UniProtKB database. Experimental observations indicated that rare and semi-common 5-mers generated stronger cellular responses in comparison with common-occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 44 publications
(43 reference statements)
2
39
0
3
Order By: Relevance
“…We followed the rationale that non-self sequences are highly immunogenic and uniquely viral epitopes should improve safety and efficacy by minimizing the risk for cross-reactions and increasing anti-viral specificity. [4][5][6] The analysis was conducted on the entire viral proteome but primarily focused on the surface spike glycoprotein (id = "QHD43416.1) because immune response against it is highly likely to exert a neutralizing effect. 2 The entire amino acid (aa) sequence of the 2019-nCoV was retrieved from https://www.ncbi.nlm.nih.gov/nuccore/MN908947 and dissected into pentapeptides overlapped by four residues for a total of n = 9661.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the rationale that non-self sequences are highly immunogenic and uniquely viral epitopes should improve safety and efficacy by minimizing the risk for cross-reactions and increasing anti-viral specificity. [4][5][6] The analysis was conducted on the entire viral proteome but primarily focused on the surface spike glycoprotein (id = "QHD43416.1) because immune response against it is highly likely to exert a neutralizing effect. 2 The entire amino acid (aa) sequence of the 2019-nCoV was retrieved from https://www.ncbi.nlm.nih.gov/nuccore/MN908947 and dissected into pentapeptides overlapped by four residues for a total of n = 9661.…”
mentioning
confidence: 99%
“…First, short peptides that are foreign to the host immune system have been experimentally validated not only as positive immunomodulants (i.e., adjuvants) in conjunction to vaccines, but are also evidenced as providing direct protection against lethal viral infections, at least in animal models. 6 Second, searching for the 107 human-foreign spike protein pentapeptides in the Immune Epitope Database (IEDB; www.iedb. org) 8 yielded a list of n = 66 epitopes (Table 1, Panel b).…”
mentioning
confidence: 99%
“…It still remains to be determined how dimerization affects UC1018 peptide as adjuvant, and covalently coupled antigen-UC1018 peptide would be another vaccine approach. Anotehr possibility to improve upon its potency would be the addition of non-HMGB1-derived antigenic amino acids (37) in an attempt to further increase adjuvanticity potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work carried out in 2009 identified 417 five amino acid primes that are not present in the universal proteome (over 6 million proteins analyzed at that time) 6 . Functional characterization of a 5-mer peptide (KWCEC) that is extremely rare within the universal proteome and absent from the human proteome, showed that it could potentially enhance immunogenicity when administered alongside an antigen 7 .…”
Section: Introductionmentioning
confidence: 99%